Answer

Verified

416.7k+ views

**Hint:**

Here, we have to find the value of the variable. We can solve the equation by using the trigonometric identity. Trigonometric equation is an equation involving one or more trigonometric ratios of unknown angles.

**Formula Used:**

We will use the following formulae:

1) Exponential Rule: \[{\left( {{a^x}} \right)^{\dfrac{1}{y}}} = {a^{\dfrac{x}{y}}}\]; \[{x^0} = 1\]

2) Logarithmic Rule: \[\log {a^b} = b\log a\]; \[{\log _a}a = 1\]

3) Trigonometric Identity: \[\sin (2\pi + \theta ) = \sin \theta ;\]

**Complete step by step solution:**

We are given with an equation \[\sin \left( {x + \dfrac{{{\pi ^3} + 2\sqrt {{\pi ^6}} }}{{{\pi ^2} + {\pi ^2}}} + {\pi ^{{\pi ^\theta }}}} \right) = \cos \left( {x + \dfrac{{{{\left( { - 1} \right)}^{16}}}}{2} - \dfrac{{{{\log }_2}\left( {\sqrt 8 } \right)}}{3}} \right)\]

First, we are converting the complex term inside the braces into a more simpler form.

Now, for the first term \[\dfrac{{{\pi ^3} + 2\sqrt {{\pi ^6}} }}{{{\pi ^2} + {\pi ^2}}} + {\pi ^{{\pi ^0}}}\], we will get

Exponential Rule: \[{\left( {{a^x}} \right)^{\dfrac{1}{y}}} = {a^{\dfrac{x}{y}}}\]and \[{x^0} = 1\]

By using the exponential rule, we have

\[ \Rightarrow \dfrac{{{\pi ^3} + 2\sqrt {{\pi ^6}} }}{{{\pi ^2} + {\pi ^2}}} + {\pi ^{{\pi ^0}}} = \dfrac{{{\pi ^3} + 2{\pi ^3}}}{{2{\pi ^2}}} + {\pi ^1}\]

Adding the like terms, we will get

\[ \Rightarrow \dfrac{{{\pi ^3} + 2\sqrt {{\pi ^6}} }}{{{\pi ^2} + {\pi ^2}}} + {\pi ^{{\pi ^0}}} = \dfrac{{3{\pi ^3}}}{{2{\pi ^2}}} + \pi \]

Dividing the term, we will get

\[ \Rightarrow \dfrac{{{\pi ^3} + 2\sqrt {{\pi ^6}} }}{{{\pi ^2} + {\pi ^2}}} + {\pi ^{{\pi ^0}}} = \dfrac{{3\pi }}{2} + \pi \]

By taking L.C.M., we will get

\[ \Rightarrow \dfrac{{{\pi ^3} + 2\sqrt {{\pi ^6}} }}{{{\pi ^2} + {\pi ^2}}} + {\pi ^{{\pi ^0}}} = \dfrac{{3\pi }}{2} + \pi \times \dfrac{2}{2}\]

\[ \Rightarrow \dfrac{{{\pi ^3} + 2\sqrt {{\pi ^6}} }}{{{\pi ^2} + {\pi ^2}}} + {\pi ^{{\pi ^0}}} = \dfrac{{3\pi }}{2} + \dfrac{{2\pi }}{2}\]

Adding the like terms, we get

\[ \Rightarrow \dfrac{{{\pi ^3} + 2\sqrt {{\pi ^6}} }}{{{\pi ^2} + {\pi ^2}}} + {\pi ^{{\pi ^0}}} = \dfrac{{5\pi }}{2}\]

Rewriting the equation, we get

\[ \Rightarrow \dfrac{{{\pi ^3} + 2\sqrt {{\pi ^6}} }}{{{\pi ^2} + {\pi ^2}}} + {\pi ^{{\pi ^0}}} = 2\pi + \dfrac{\pi }{2}\]

Now,

By Rewriting the equation, we get

\[ \Rightarrow \dfrac{{{{( - 1)}^{16}}}}{2} - \dfrac{{{{\log }_2}\sqrt 8 }}{3} = \dfrac{1}{2} - \dfrac{{{{\log }_2}\sqrt {{2^3}} }}{3}\]

\[ \Rightarrow \dfrac{{{{( - 1)}^{16}}}}{2} - \dfrac{{{{\log }_2}\sqrt 8 }}{3} = \dfrac{1}{2} - \dfrac{{{{\log }_2}{2^{\dfrac{3}{2}}}}}{3}\]

Logarithmic Rule: \[\log {a^b} = b\log a\]

By using logarithmic rule, we get

\[ \Rightarrow \dfrac{{{{( - 1)}^{16}}}}{2} - \dfrac{{{{\log }_2}\sqrt 8 }}{3} = \dfrac{1}{2} - \dfrac{{\dfrac{3}{2}{{\log }_2}2}}{3}\]

\[ \Rightarrow \dfrac{{{{( - 1)}^{16}}}}{2} - \dfrac{{{{\log }_2}\sqrt 8 }}{3} = \dfrac{1}{2} - \dfrac{{3{{\log }_2}2}}{{2 \cdot 3}}\]

Dividing both the terms, we get

\[ \Rightarrow \dfrac{{{{( - 1)}^{16}}}}{2} - \dfrac{{{{\log }_2}\sqrt 8 }}{3} = \dfrac{1}{2} - \dfrac{{{{\log }_2}2}}{2}\]

Logarithmic Rule: \[{\log _a}a = 1\]

By using logarithmic rule, we get

\[ \Rightarrow \dfrac{{{{( - 1)}^{16}}}}{2} - \dfrac{{{{\log }_2}\sqrt 8 }}{3} = \dfrac{1}{2} - \dfrac{1}{2}\]

\[ \Rightarrow \dfrac{{{{( - 1)}^{16}}}}{2} - \dfrac{{{{\log }_2}\sqrt 8 }}{3} = 0\]

Now, by using the equation and substituting the values, we get

\[ \Rightarrow \sin \left( {x + \dfrac{{{\pi ^3} + 2\sqrt {{\pi ^6}} }}{{{\pi ^2} + {\pi ^2}}} + {\pi ^{{\pi ^\theta }}}} \right) = \cos \left( {x + \dfrac{{{{\left( { - 1} \right)}^{16}}}}{2} - \dfrac{{{{\log }_2}\left( {\sqrt 8 } \right)}}{3}} \right)\]

\[ \Rightarrow \sin \left( {x + 2\pi + \dfrac{\pi }{2}} \right) = \cos \left( {x + 0} \right)\]

\[ \Rightarrow \sin \left( {2\pi + \dfrac{\pi }{2} + x} \right) = \cos \left( x \right)\]

Trigonometric Identity: \[\sin (2\pi + \theta ) = \sin \theta \]

Now, by using the trigonometric identity, we get

\[ \Rightarrow \sin \left( {\dfrac{\pi }{2} + x} \right) = \cos \left( x \right)\]

This equation holds true for all \[x \in {\bf{R}}\].

So, \[x = 0,\dfrac{\pi }{2}\].

**Therefore, the two values of \[x\] that satisfy the equation are \[0,\dfrac{\pi }{2}\]**

**Note:**

We should make sure of using the trigonometric identity, exponential rule, the logarithmic rule at the right place. A trigonometric equation will also have a general solution expressing all the values which would satisfy the given equation, and it is expressed in a generalized form in terms of ‘n’. Thus the trigonometric equation always possess various solutions.

Recently Updated Pages

what is the correct chronological order of the following class 10 social science CBSE

Which of the following was not the actual cause for class 10 social science CBSE

Which of the following statements is not correct A class 10 social science CBSE

Which of the following leaders was not present in the class 10 social science CBSE

Garampani Sanctuary is located at A Diphu Assam B Gangtok class 10 social science CBSE

Which one of the following places is not covered by class 10 social science CBSE

Trending doubts

Which are the Top 10 Largest Countries of the World?

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

How do you graph the function fx 4x class 9 maths CBSE

In Indian rupees 1 trillion is equal to how many c class 8 maths CBSE

The Equation xxx + 2 is Satisfied when x is Equal to Class 10 Maths

Give 10 examples for herbs , shrubs , climbers , creepers

Why is there a time difference of about 5 hours between class 10 social science CBSE

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

What is BLO What is the full form of BLO class 8 social science CBSE